Bilingual dictionary of Islamic terminology in finance, banking and halal English-Malay = Kamus istilah kewangan, perbankan dan halal dalam Islam Inggeris-Melayu - Dollah, Nafi@Hanafi (Hanafi Dollah, 2019)
The " Bilingual Dictionary of Islamic Terminology in Finance, Banking and Halal: English - Malay” came seeking two languages. It is a synthesis and diverse dictionary, and also creative. Malay language gives a new and innovative sense, especially Malaysia as a global leader in Islamic banking. Indeed, this Islamic terms dictionary has benefited from the previous dictionaries in halal, financial and economic terms that using the approach of synthesis and creativity. This dictionary has also benefited from the jurisprudential and contemporary jurisprudence books that have stood on Islamic transactions and touched on the door of Islamic banks.